Hypoxic Liver Injury as Predictor of Major Adverse Cardiac Events in Acute Myocardial Infarction patients admitted to Intensive Coroner Care Unit of Cipto Mangunkusumo National General Hospital - Muhadi, Muhadi; Prihartono, Nurhayati Adnan (UI Scholars Hub, 2018)
Introduction. Major adverse cardiac events (MACE) is a complicating myocard infarct which consist of acute heart failure, cardiogenic shock, and fatal arrhytmia. An accurate, easy and cost-effective biomarker is needed to predict MACE and mortality in patients with myocard infarct. Hypoxic liver injury (HLI) is a potential biomarker using serum glutamic-oxaloacetic transaminase (SGOT) level as the parameter. This study is aimed to discover HLI’s role in predicting MACE in non ST elevation myocard infarct (NSTEMI). Methods. This study was designed as cross sectional to predict MACE and prospective cohort for survival analysis. Study population was all NSTEMI patients admitted to ICCU of Cipto Mangunkusumo Hospital and study sample were NSTEMI patients admitted to ICCU of Cipto Mangunkusumo Hospital that meets all criteria during 2006-2016. Cut-off level of SGOT for HLI to predict MACE and mortality was analyzed using ROC curve and AUC. Survival analysis was done using Kaplan Meier curve and the difference was tested with log-rank. Results. A total of 277 subjects were included in this study. Incidence of MACE in this study was 51.3% (acute heart failure 48.4%, fatal arrhytmia 6.5%, and cardiogenic shock 7.2%). The mortality rate was 6.13%. The median of SGOT level on all subject was 35 U/L, 40 (range 8-2062) U/L in subjects with MACE and 31 (range 6-1642) U/L in subjects without MACE (p = 0.003). Cut-off level for SGOT used to predict MACE was 101 U/L (sensitivity 21.8%; specificity 89.6%; POR 2.727 (CI 95% 1.306- 5.696), p = 0.006). In multivariate analysis, HLI was insignificantly related to MACE. Cut-off level for SGOT used to predict survival was 99 U/L (sensitivity 23.5%; specificity 83.8%; likelihood ratio +1.46). There were no significant difference of survival between groups with HLI level below and above the cut-off SGOT level. Conclusion. Hypoxic liver injury (HLI) cannot be used to predict MACE in NSTEMI patients unless combined with other variables. There is no significant difference of survival between subjects with or without HLI.